The Effectiveness of a Bilingual Digital Pop-Up Book in Improving Elementary School Students’ Reading Comprehension of Narrative Texts (Fairy Tales) - Aida Salsabila Aulia; Petra Kristi Mulyani (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
Elementary school students’ narrative reading comprehension skills remain suboptimal, particularly in understanding intrinsic story elements, plot, explicit information, inference, and moral messages. This study aimed to develop and examine the feasibility and preliminary effectiveness of a PowerPoint-based bilingual digital pop-up book for teaching narrative fairy tale texts to fourth-grade elementary school students. The research employed a Research and Development method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. A small-group trial was conducted to assess the readability and practicality of the media, while a large-group trial was used to evaluate its preliminary effectiveness through a one-group pretest–posttest design. Data were collected through expert validation sheets, teacher and student response questionnaires, and reading comprehension tests. The validation results indicated that the media was categorized as highly feasible, with scores of 96.6% from media experts and 86.6% from material and language experts. The paired sample t-test showed a significant difference between pretest and posttest scores with a significance value of 0.001 < 0.05. The N-gain score of 0.59 was categorized as moderate. In addition, teacher responses reached 93.3% and student responses reached 97.2%, indicating that the media was highly practical for classroom use. These findings demonstrate that the bilingual digital pop-up book is feasible and effective in improving elementary school students’ narrative reading comprehension.